Emergency geriatric surgical admissions. Issue 6134 (5th August 1978) - Salem, R; Devitt, P; Johnson, J; Firmin, R
Abstract : The emergency surgical work load created by patients aged 80 and over in a district hospital was assessed and the results of treatment examined. Over one year 248 patients aged 80 or over were admitted as emergencies, and the overall mortality rate was 21·8%. When terminal disease was excluded mortality rate was 12·5%. These elderly patients had an average length of stay in the acute surgical ward of 14·7 days compared with a mean of 8·4 days for all patients, and all but seven patients were discharged to their original place of referral. Elderly patients do exacerbate the bed shortage in acute surgical wards because they tend to stay longer than younger patients, but these elderly surgical patients imposed only a small load on the inpatient geriatric services, as 78% were discharged straight to their own homes and a further 17% went home after a period on the surgical convalescent wards.